Does sprint interval training cause interference in concurrent training? A meta-analysis study - Ferraro-Farro, D.; Bandeira-Guimarães, M.; Blanco-Rambo, E.; Ferreira Vieira, A.; Lusa Cadore, E.; Benítez-Flores, S. (International Journal of Sports Medicine, 2026)
The interference effect associated with concurrent training has been widely debated. A recent model suggests that including sprint interval training as the endurance component may attenuate this effect. However, studies examining the impact of sprint interval training-based concurrent training on neuromuscular and cardiorespiratory adaptations are limited. This systematic review with meta-analysis evaluated the effects of concurrent training programs including sprint interval training on strength, hypertrophy, maximum oxygen consumption, and sprint performance. Searches were conducted in PubMed, Embase, and SPORTDiscus, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines. Randomized controlled trials in healthy adults (=18 y) comparing sprint interval training-based concurrent training with resistance training alone, including at least six supervised sessions over 2 weeks, were eligible. Nine studies (177 participants) met the inclusion criteria. Pooled analyses showed no significant differences between sprint interval training combined with resistance training and resistance training alone for lower-body strength (standardized mean difference=0.01; p = 0.94), upper-body strength (standardized mean difference=- 0.06; p = 0.83), jump performance (standardized mean difference=0.11; p = 0.11), or sprint performance (standardized mean difference=- 0.01; p = 0.95). However, sprint interval training combined with resistance training significantly improved maximum oxygen consumption compared with resistance training alone (standardized mean difference=0.78; p = 0.001). Sensitivity analysis revealed greater jump gains with short sprint protocols (=10 s; standardized mean difference=0.41; p = 0.025). These findings indicate that introducing sprint interval training into concurrent training enhances cardiorespiratory fitness without compromising strength or power and may potentiate jump performance when short sprints are used.